Juridical Analysis of Dissenting Opinions of Constitutional Judges in Constitutional Court Decisions (Jurnal Scientia Indonesia, 2022)
This research will raise the issue that will be studied is, First, the regulation of dissenting opinion in the Constitutional Court's Event Law.  Second, the legal power of dissenting opinion in the Constitutional Court Decision.  Third, the legal implications of dissenting opinion in the Constitutional Court Decision. This resulted in the conclusion First, the arrangement of dissenting opinions in the constitutional court's guidelines in this case in the FMD cannot be found as a whole.   The arrangement of dissenting opinion in the PMK independence of constitutional judges in conveying their opinions is still maintained.  Second, explicitly, there is no setting on dissenting opinion. The phrase used in Law No. 24 of 2003 concerning the Constitutional Court is "the opinion of different members of the panel of judges". Third, the legal implications of dissenting opinion in the Constitutional Court's decision are legal uncertainty, violation of the hierarchy of laws and regulations, and the absence of legal order. The formulation of dissenting opinion is necessary to clarify its position in the law of events in the Constitutional Court. This can only be done if the legal instruments that govern it give full legitimacy to constitutional judges in dissenting. The author's advice in this study is   to strengthen the legal power  of dissenting opinion, as a preventive measure against future legal reforms to ensure certainty, justice. and the usefulness of the law for the whole society